Analisis Minat Belajar Dan Kompetensi Guru Terhadap Keterampilan Kerja Siswa Program Keahlian Teknik Gedung SMK Negeri 1 Tomohon - Daud, Metsi (Peneliti.net, 2024)
This research aims to test the significance of (1) the influence of students' learning interest on students' work skills, (2) the influence of teacher competence on students' work skills, and (3) the influence of students' learning interest and teacher competence together on students' work skills. This research design is quantitative research with a correlational research approach. The research objects were students of SMK Negeri 1 Tomohon with a total of 40 students. The contribution of interest in learning to work skills was 9.90%. The contribution of teacher competence to work skills is 26.50%. The contribution of student learning interest and teacher competency together to student work skills is 26.80%. In increasing students' interest in learning and teacher competence in the form of interest, enjoyment, attention, willingness, concentration and awareness. knowledge to manage learning planning, the learning process, can improve students' work skills which will increase the level of ability that students have achieved after following the learning process for a certain time in the form of using tools, analyzing, designing, technical instructions for work, accuracy in completing work. Or in improving work skills students must pay attention to the competence of teachers who actually make a significant contribution.